Validación de modelos virtuales a partir de modelos reales - Fuentes-Víquez, Hugo Ignacio (Instituto Tecnológico de Costa Rica, 2016)
The structural analysis programs present several ways to model a structure but not always are used properly. The project pretend prove the validity of the virtual models frame and shell to represent the behavior of beam elements validating the results from real prototypes varying the span/depth ratio using the displacement as calibration parameter. It was used wood of Radiata pine, which was characterized to know his mechanics characteristics on flexion, besides it was calculated of different ways the elasticity modulus (E) to find the one that represent the displacement of the real prototypes of proper way comparing them with the obtained in the virtual models. For the shell elements it was realized an aspect analysis for the finite elements and a sensibility analysis to determine the influential factors on his results. The mechanical characteristics in flexion obtained were inferior to those reported by radiata pine producers. The most precise methods to calculate the modulus of elasticity were that implicated the load and displacement in the proportional limit. Both virtual models are valid, but the frame is more efficient because it doesn’t need a preprocessing to start the analysis while the shell it does require it and should be more careful doing it. The quantities of the finite elements to use and his respective aspect ratio are factors that affect the result of the shell models.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Construcción, 2016.
Keywords: Diseño; Métodos Numéricos; Programas de Computación; Análisis; Ecuaciones; Propiedades de los materiales